2021
DOI: 10.1111/jcpt.13475
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for skin disorders caused by anti‐epidermal growth factor receptor antibody drugs and examination of methods for their avoidance

Abstract: What is known and Objective: Cancer drug treatment is often discontinued because of skin disorder aggravation. However, information on risk factors for skin disorders caused by anti-epidermal growth factor receptor (EGFR) antibody drugs is limited.The aim of this study was to analyse the factors associated with skin disorders caused by anti-EGFR antibody drugs and establish a method to minimize such aggravations. Methods:We retrospectively examined 67 colorectal cancer patients treated with anti-EGFR antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The target patients were classified into two groups based on body weight, extracted as a risk factor from our previous report [ 11 ]. Patient characteristics for each group, classified by body weight, are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The target patients were classified into two groups based on body weight, extracted as a risk factor from our previous report [ 11 ]. Patient characteristics for each group, classified by body weight, are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Patients with skin diseases, including psoriasis or atopic dermatitis, were excluded from the study. This study included patients who were previously enrolled in a study that identified high body weight as a risk factor for developing acneiform rash during anti-EGFR antibody therapy [ 11 ]. Therefore, as in the previous study, the target patients were classified based on body weight, which was the risk factor for developing acneiform rash.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase III clinical trial conducted in Canada in 2016 showed that the preventive use of minocycline (100 mg twice a day for 1 month) before erlotinib did not reduce the incidence of rashes but reduced the incidence of grade 3 skin toxicity while not affecting efficacy ( 177 ). Takahashi et al ( 120 ) also showed that the grade of acneiform rash was lower after preventive use of minocycline. Meanwhile, Ichiki et al ( 178 ) found that prophylactic use of minocycline (50 mg twice a day for 4 weeks) reduced rashes and paronychia induced by afatinib.…”
Section: Therapeutic Strategies For Skin Toxicitymentioning
confidence: 96%
“…Another study showed that patients with high sebaceous gland activity and sebum secretion were more sensitive to EGFR inhibitors and developed acneiform rash more frequently (119). Takahashi et al (120) also found that men and high-weight patients who used EGFR inhibitors were more susceptible to severe skin toxicity. High male hormones, high sebum secretion, and smoking (more prevalent in males than females) are risk factors causing male lung cancer patients to have more severe adverse skin reactions.…”
Section: Factors Leading To Fatal Skin Toxicitymentioning
confidence: 98%